Review of Community Solar in the United States of America - Aldarsi, Eyad; Singh, Rajendra (New Energy Exploitation and Application, 2024)
Community solar is a concept where a large number of entities (consumers, businesses, charitable foundations, investors, etc.) can participate with or without having 100% ownership of the solar hardware. The objective of this paper is to provide an in-depth review of community solar. Although we have kept the global picture in mind, the United States has been our focus. The authors have provided details of the overall role of photovoltaics and battery-based power networks in global electrical power generation. Based on published reviews and research papers, the authors have analyzed the operation of community solar, ownership models and business models used in community solar projects. Based on the published results, the authors found that community solar might grow exponentially. However, due to ultra-small scale power level, this concept has not played a significant role as compared to residential, commercial, industrial and utility-scale use of solar photovoltaics. For the growth of community solar, the authors have proposed a new concept where new constructions can provide large-scale use of community solar projects. The proposed concept is off-grid and can be implemented without the introduction of any new public policy. In conclusion, the proposed concept can play a major role in providing green electrical power for new loads that also include the charging of electrical vehicles.